Irrigation management in Nepal: Research papers from a National Seminar, Bharatpur, Nepal, 4-6 June 1987 - International Irrigation Management Institute (International Irrigation Management Institute, 1988)
Numerous field studies related to irrigation management have been conducted in Nepal since the last national seminar on irrigation issues in 1983. The relationship between organizational structure and resource mobilization was the topic of several. Another examined changes in organization and resource mobilization as property relationships and water rights changed when systems expanded and allowed new members. Concern for improving intervention strategies to existing farmer-managed irrigation systems has stimulated work on finding methods for quickly collecting data for identification and assessment of systems where substantial gains can be made by giving assistance. Numerous case studies have expanded the information available on management of operation and maintenance in both farmer- and agency-managed systems. These seminar papers report the findings of eleven of the studies.